2011
DOI: 10.1111/j.1468-2311.2010.00647.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Brief Intervention of Detainees for Alcohol Use: A Social Crime Prevention Approach to Combating Alcohol‐Related Crime?

Abstract: Irresponsible and excessive consumption of alcohol and the associated problems it carries in its wake have become one of the key concerns for central government in terms of community safety, especially in the night-time economy. In response to the Alcohol Harm Reduction Strategy for England (Department of Health 2007), the Department of Health (DoH) has announced a series of measures of which one is to pilot screening and intervention for alcohol use in a variety of locations, including criminal justice settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
1
17
0
Order By: Relevance
“…Three had a low risk of bias (Hopkins and Sparrow, 2006;Brown et al, 2010;Barton, 2011). One study had a low risk of bias (Brown et al, 2010) and the others an unsure risk of bias.…”
Section: Police Custody Suitesmentioning
confidence: 98%
See 3 more Smart Citations
“…Three had a low risk of bias (Hopkins and Sparrow, 2006;Brown et al, 2010;Barton, 2011). One study had a low risk of bias (Brown et al, 2010) and the others an unsure risk of bias.…”
Section: Police Custody Suitesmentioning
confidence: 98%
“…Five studies were identified relating to the police custody suite setting (Hopkins and Sparrow, 2006;Brown et al, 2010;Barton, 2011;Kennedy et al, 2012;McCracken et al, 2012). Three had a low risk of bias (Hopkins and Sparrow, 2006;Brown et al, 2010;Barton, 2011).…”
Section: Police Custody Suitesmentioning
confidence: 99%
See 2 more Smart Citations
“…An extensive body of international evidence demonstrates a link between alcohol consumption, risky behaviours and criminal activity ( Miller et al , 2006 ; Newbury-Birch et al , 2009 ; Barton, 2011 ; Bouchery et al , 2011 ; Kennedy et al , 2012 ; Kinner et al , 2015 ; Needham et al , 2015 ; Orr et al , 2015 ; de Andrade et al , 2016 ). Alcohol-related crimes have been estimated to cost £11 billion per annum in the UK ( Home Office, 2013 ) and between $73 and $84 billion in the USA ( Miller et al , 2006 ; Bouchery et al , 2011 ).…”
Section: Introductionmentioning
confidence: 99%